Identification of Ppk26, a DEG/ENaC Channel Functioning with Ppk1 in a Mutually Dependent Manner to Guide Locomotion Behavior in Drosophila. - Gorczyca, D.A.; Younger, S.; Meltzer, S.; Kim, S.E.; Cheng, L.; Song, W.; Lee, H.Y.; Jan, L.Y.; Jan, Y.N. (Cell reports, 2014)
A major gap in our understanding of sensation is how a single sensory neuron can differentially respond to a multitude of different stimuli (polymodality), such as propio- or nocisensation. The prevailing hypothesis is that different stimuli are transduced through ion channels with diverse properties and subunit composition. In a screen for ion channel genes expressed in polymodal nociceptive neurons, we identified Ppk26, a member of the trimeric degenerin/epithelial sodium channel (DEG/ENaC) family, as being necessary for proper locomotion behavior in Drosophila larvae in a mutually dependent fashion with coexpressed Ppk1, another member of the same family. Mutants lacking Ppk1 and Ppk26 were defective in mechanical, but not thermal, nociception behavior. Mutants of Piezo, a channel involved in mechanical nociception in the same neurons, did not show a defect in locomotion, suggesting distinct molecular machinery for mediating locomotor feedback and mechanical nociception.